2009
DOI: 10.1002/art.24332
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/ENHANCER binding protein β mediates expression of matrix metalloproteinase 13 in human articular chondrocytes in inflammatory arthritis

Abstract: Objective. To determine the function of CCAAT/ enhancer binding protein ␤ (C/EBP␤) in the expression of matrix metalloproteinase 13 (MMP-13) in chondrocytes in inflammatory arthritis.Methods. Cartilage obtained from patients with rheumatoid arthritis and osteoarthritis was immunostained for expression of C/EBP␤ or MMP-13. Interleukin-1␤-or tumor necrosis factor ␣ (TNF␣)-stimulated chondrocytes were subjected to Western blotting and real-time reverse transcriptase-polymerase chain reaction (RT-PCR). MMP-13 prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 45 publications
(42 reference statements)
0
34
0
Order By: Relevance
“…7). MMP13 is known to be a major degrading enzyme of COL2A1, and we previously reported that C/EBP␤ is a direct inducer of MMP13 (22). Increase in the expression of MMP13 could be involved in the degradation of COL2A1 in C/EBP␤-infected tibias.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…7). MMP13 is known to be a major degrading enzyme of COL2A1, and we previously reported that C/EBP␤ is a direct inducer of MMP13 (22). Increase in the expression of MMP13 could be involved in the degradation of COL2A1 in C/EBP␤-infected tibias.…”
Section: Discussionmentioning
confidence: 80%
“…C/EBP␤ is known to be induced by pro-inflammatory cytokines such as IL-1␤, IL-6, and TNF-␣, and it is expressed in arthritic cartilage (15,20,22). It has been suggested that C/EBP␤ also plays a role in the repression of COL2A1 in response to inflammatory signals (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C/EBP␤-binding sites in the Adamts1 promoter have also been involved in its induction by progesterone receptor-mediated activation of granulosa cells (29), further supporting the relevance of C/EBP␤ proteins in the regulation of Adamts-1 expression. Furthermore, active C/EBP␤ proteins have been linked to the expression of other metalloproteinase proteins, including MMP-3, MMP-13, and Adamts-5, during arthritic tissue remodeling (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…The Gadd45␤ and C/ebp␤ knock-out mice display similar phenotypic changes in the embryonic growth plate, characterized by a delay in terminal chondrocyte differentiation along with decreased expression of genes linked to this process, including Col10a1 and Mmp13 (8,37,69). In addition, the embryonic limbs of C/ebp␤ knock-out mice display impaired osteogenesis (53).…”
Section: Gadd45␤ Regulation Of Genes Involved In Terminal Chondrocytementioning
confidence: 99%